If a+b+c =0 then a3+b3+c3 = 3abc in this question let a= (p-q) ,b= (q-r) , c= (r-p) than a+b+c = p - q + q- r + r- p = 0 so
(p-q)3 + ( q-r)3+ (r-p)3 = 3 (p-q)(q-r)(r-p)

This is the shortest way to do these type of questions .................................................................................................................................

Answers

2014-07-05T14:10:15+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let a= (p-q) , b= (q-r), c= (r-p) now a+b+c= p-q+q-r+r-p. =0 we know that if a+b+c =0 then a^3 + b^3 + c^3 =0 so (p-q)^3 + (q-r)^3 + ( r-p)^3 =0 answer
0
Hope it helps you this is the shortest way of doing this type of questions
plz mark as best